The future of agricultural landscapes, Part I - Bohan, David A.; Vanbergen, Adam J. (Advances in ecological research, 2020)
"Advances in Ecological Research, Volume 63, the latest release in this ongoing series includes specific chapters on Tropical Ecosystems in the 21st Century. Chapters in this volume cover topics such as Landscape-scale expansion of agroecology to enhance natural pest control: a systematic review and Ecosystem services and the resilience of agricultural landscapes"--publisher's web page, viewed October 27, 2020.